Freiräumen : Entwerfen als Landschaftsarchitektur. - Bernard, Stefan (De Gruyter, 2014)
"What does the landscape architect actually do as a design?" The authors investigate this seemingly simple question: How are locations and spaces created in the open air, how are paths routed and boundaries set, how are hard and soft materials used? Drawing on practical and theoretical experience, this introduction, often used as a textbook, reveasls the central components of design and the intellectual paths followed in the design process.